2015
DOI: 10.1039/c5dt02018b
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA/RNA bulges by antimicrobial and antitumor metallohelices

Abstract: Bulged structures have been identified in nucleic acids and have been shown to be linked to biomolecular processes involved in numerous diseases. Thus, chemical agents with affinity for bulged nucleic acids are of general biological significance. Herein, the mechanism of specific recognition and stabilization of bulged DNA and RNA by helical bimetallic species was established through detailed molecular biophysics and biochemistry assays. These agents, known as 'flexicates', are potential mimetics of α-helical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
(87 reference statements)
3
23
0
1
Order By: Relevance
“…We have previously concluded that the induction of DNA damage is not involved in the mode of action of earlier flexicates, despite particular examples binding in a cell free environment. 20 , 32 , 33 We investigated the effect that the new flexicates had on the denaturation temperature ( T m ) of ct-DNA to screen for any indications of DNA binding.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously concluded that the induction of DNA damage is not involved in the mode of action of earlier flexicates, despite particular examples binding in a cell free environment. 20 , 32 , 33 We investigated the effect that the new flexicates had on the denaturation temperature ( T m ) of ct-DNA to screen for any indications of DNA binding.…”
Section: Resultsmentioning
confidence: 99%
“…[107] Detailed research has also implicated M 2 L 3 complexes in selective G quadruplex binding, [108] and at DNAb ulges. [109,110] An umber of studies have highlighted that due to the polycationic charge of many metal-organic complexes,they are efficiently able to condense polyanionic DNAa nd inhibit natural enzymatic processes. [103,111] Them ode of action of these small metal-organic constructs is however not limited to DNAi nteractions,a nd biophysical measurements have shown that some flexicates do not interact significantly with DNA.…”
Section: Reviewsmentioning
confidence: 99%
“…Mittlerweile hat die Modifizierung von 23 Helikate mit verbesserter Erkennung von Dreiwege‐Kreuzungen hervorgebracht . Ausführliche Forschungen befassten sich auch mit M 2 L 3 ‐Komplexen zur selektiven Bindung an G‐Quadruplexe und DNA‐Ausbuchtungen . In einer Reihe von Studien wurde betont, dass viele Metall‐organische Komplexe wegen ihres polykationischen Käfigs effizient in der Lage sind, polyanionische DNA zu verdichten und natürliche enzymatische Vorgänge zu hemmen …”
Section: Synthetische Anordnungenunclassified